Patient-Determined Outcomes After Arthroscopic Margin Convergence Rotator Cuff Repair - Keith M. Baumgarten, M.D (Elsevier, 2020)
Purpose: To determine whether patients who require margin convergence would have equivalent postsurgical patient-determined scores compared with patients with standard rotator cuff repair. The secondary purpose of this study was to determine whether the short-term results found for patients with margin convergence repairs would be durable through medium-term follow-up. Methods: A retrospective analysis of patients undergoing arthroscopic rotator cuff repair was performed to examine the effects of marginal convergence on patient-determined outcomes (Western Ontario Rotator Cuff Index, American Shoulder and Elbow Surgeons score, Simple Shoulder Test, Single Assessment Numeric Evaluation, and Shoulder Activity Level). Patient-determined outcomes in patients who had margin convergence repairs were compared with patients who had standard rotator cuff repair. Prospective follow-up of patients that had margin convergence repairs was performed to determine whether patient-determined outcomes deteriorated over time. Results: Two-hundred-seventy-two patients had standard rotator cuff repairs and 9 patients had margin convergence rotator cuff repair (3.2%). All patients had significant improvements in their Western Ontario Rotator Cuff Index, American Shoulder and Elbow Surgeons score, Simple Shoulder Test, and Single Assessment Numeric Evaluation. Patients requiring margin convergence rotator cuff repair had similar preoperative and postoperative scores compared with patients with a standard rotator cuff repair. At a mean follow-up of 7.5 years, there was no change in outcome scores compared with the early follow-up time point (mean 3.3 years) for patients undergoing margin convergence. Conclusions: Arthroscopic margin convergence repair techniques along with the treatment of concomitant pathologies result in similar patient-determined outcomes compared with standard rotator cuff repair techniques. These results appear to be durable and do not deteriorate from short-term to medium-term follow-up. Level of evidence: III: Retrospective comparative study